Implementasi Metode Demonstrasi untuk Meningkatkan Pemahaman Anak Tentang Tata Cara Sholat Dhuha - Sa'diyah, Nur Laila; Lina, Helina Himmatul Ulya; Sa'adah, Latifatus (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood children's understanding of the procedures for Dhuha prayer is still low because the learning process is predominantly verbal, so a method that suits the characteristics of children's learning is needed. This study aims to describe the implementation of the exposure method in improving children's understanding of the procedures for Dhuha prayer at RA Assalafiyah Gedongsari Blora. This study uses a qualitative descriptive approach with children aged 5-6 years old at RA Assalafiyah Gedongsari Blora as research subjects, while the informants are the principal and class teachers. Data were collected through observation, interviews, and documentation, then analyzed through the stages of reduction, presentation, and verification of conclusions. The results of the study show that children's understanding of the procedures for Dhuha prayer has increased quite significantly after the implementation of the maintenance method. The results of the study show that children's understanding of the procedures for Dhuha prayer has increased after the implementation of the savings method. Children who understood the procedures for Dhuha prayer were initially only around 5 children, then increased to an average of 13 children. This shows that the enhancement method is effective in helping early childhood children understand the procedures for Dhuha prayer better. In conclusion, the reinforcement method has proven effective in improving early childhood's understanding of the procedures for performing the Dhuha prayer as a whole.